Assessing the relationship between internet usage and technostress: a moderated mediation model - Abdullah, Haslinda; Bajwa, Ruqia Safdar; Wan Jaafar, Wan Munira; Abu Samah, Asnarulkhadi (Pakistan Home Economics Association, 2023)
Purpose: Technostress or technology-induced stress is well-known in the literature among working people. Although technology is becoming more prevalent in higher education, there is still a lack of research investigating the predictors of technostress and its impact on university students. The current study explored: (i) the mediating role of problematic internet use (PIU) in the relationship between internet usage and technostress and (ii) the moderation of personality type on the relationship between internet usage and PIU among university students in Pakistan. Design/Methodology/Approach: For this correlational study, participants (n=165) were bachelor's and master's students from two public universities in Pakistan. A purposive sampling technique was used and SmartPLS was used for analysis. Findings: Problematic internet usage partially mediated the relationship between internet usage and technostress among university students. Conscientiousness moderated the relationship between internet usage and problematic internet use negatively whereas neuroticism moderated the relationship positively. Conclusion: The findings are an essential landmark for the consequences of problematic internet usage and the presence of technostress among students. Workshops and specialized programs are necessary to promote awareness among university students and proper counseling services to reduce the adverse effects of internet usage, problematic internet usage and technostress.